Comparative study on sexual and reproductive health of adolescents with and without aids: is there a difference in knowledge between the two groups? - Cordellini, Júlia Valéria Ferreira; Rodrigues, Cristina de Oliveira; Weber, Lidia Natalia Dobrianskyj; Tahan, Tony Tannous; Bermudez, Beatriz Elizabeth Bagatin Veleda; Ribeiro, Clea Elisa Lopes; Rossoni, Andrea Maciel de Oliveira (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Currently we are facing the challenge to deal with the first generation of adolescents HIV+, infected by vertical transmission. This is new, and creates the need to improve attention to self-care and knowledge on sexual and reproductive health. Issues like the exercise of sexuality, contraception, pregnancy, sexually transmitted diseases (STD), are not enough debated among professionals, families and adolescents, despite their importance, concerning the affective and sexual discoveries typical of that age. Objective: To assess and compare the knowledge among adolescents HIV+ and HIV-, the guidance received on sexual and reproductive health and their sexual behavior, in order to better assist an integral health attention. Methods: A prospective, quali-quantitative, observational, analytical and cross-sectional study that took place during one year at the public hospital of an university in Curitiba, interviewing 61 adolescents HIV+ and 61 adolescents HIV- after their outpatient attendance. A questionnaire with objective multi-choice questions, as well as open-ended questions thought to stimulate free narratives was the base of data acquisition. Statistical analysis have considered the adolescents HIV+ and HIV- matched by age, gender and education. To evaluate differences on continuous variables, Student’s t-test for normal distribution and Mann-Whitney test for asymmetric distribution were the tools. For categorical variables: Fisher exact tests and chi-square of Pearson. The analysis of answers for the openended questions was based on categorization of semantic equivalence. Significance level of 5% for all tests. Main variables of study in the amount enough to allow comparisons have driven the sample estimation, with less than 5% of significance level and minimum test power of 95%. Results: The study showed that adolescents don’t have good enough knowledge about reproductive health in both groups (p=0.01). They have initiated sexual activity at about 15 years old, they report using condoms, but not the habit of picking them up. The group of HIV + have expressed more opinions about the sexual and reproductive rights, they have received less guidance on emergency contraception (p<0.001); they “hook-up” and dated less than HIV- group. Conclusion: The lack of knowledge of adolescents on reproductive health is greater than about sexual health and both groups reported the habit of not getting condoms. The HIV+ group had more opinions about sexual and reproductive rights, received less guidance on emergency contraception, “hooked-up” and dated less than the HIV- group. The knowledge about sexual rights and sexuality, and the guidance provided to both groups of teenagers, didn’t seem to be adequate to make protective sexual attitudes preventing STD.